Testing the Effectiveness of Pandan Wangi Leaf Extract (Pandanus amaryllifolius Roxb) as an Insecticide against House Flies (Musca domestica) - Putri, Zulfina Eka (Contributions of Central Research Institute for Agriculture, 2023)
One of the causes of poor environmental conditions is the increasing number of infectious diseases caused by vectors. Flies are vectors that act as intermediaries for disease transmission, so their presence needs to be controlled. Therefore control is really needed, one of the controls that can be done is vegetable pesticides. This biopesticide consists of active ingredients that are environmentally friendly because their contents are biodegradable. This research aims to determine the effectiveness of fragrant pandan leaf extract as an insecticide against house flies. This type of research is pure experimental research with a Posttest Only Control Group Design, which is a design that does not use a pretest on the sample before treatment. The results of this study show that the lowest Musca domestica mortality rate was at a concentration of 5%, namely 1 animal (15%) and the highest mortality was at a concentration of 15%, namely 13 individuals. The ANOVA test results show that p-value = 0.000 (p<0.05) so Ha is accepted. And the LC50 probit analysis results were 90.8657 ppm < 1000 µg/mL (ppm). The parameters observed in this study were the death of adult flies after being exposed to fragrant pandan leaf extract with each concentration in percent (%) and the death of flies in the control group. Fly death is characterized by not moving or not responding to stimuli. Observations were carried out every 60 minutes until the 24th hour after treatment in accordance with WHO standards, namely regarding standards for research on insects. Based on the description above, testing the effectiveness of the botanical insecticide fragrant pandan leaf extract against house flies has been carried out for approximately 4 months. So it can be concluded that fragrant pandan leaf extract is toxic to house flies, requiring further research regarding the concentration of related things, which is the most effective and efficient in killing house flies.